Improvement of the production of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate‐co‐4‐hydroxybutyrate) terpolyester by manipulating the culture condition - Nursolehah Abd Aziz; Coswald Stephen Sipaut @ Mohd Nasri; Amirul Al‐Ashraf Abdullah (John Wiley, 2012)
BACKGROUND: The aim of this work is to enhance the production of terpolyester poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate‐co‐4‐hydroxybutyrate) (P(3HB‐co‐3HV‐co‐4HB)) produced by a locally isolated bacterium, Cupriavidus sp. USMAA2‐4. The monomer composition was varied by supplementing different carbon precursors and by manipulating the culture condition through one‐stage cultivation. The effect of C/N ratio and different concentrations of carbon source and precursors were investigated in order to produce higher content of this terpolyester. Although research on this biodegradable polyester is abundant, studies on terpolyester P(3HB‐co‐3HV‐co‐4HB) are still limited.